Timed-Release Silica Microcapsules for Consistent Fragrance Release in Topical Formulations - Junseok Yeom; Minseo Kang; Areum Goh; Jeonghoon Jeon; Woo Sun Shim; Nae Gyu Kang (Applied Sciences)
Microcapsules are widely utilized in various applications to preserve active ingredients for prolonged durations while enabling controlled release. However, limited release of active ingredients often hampers their effectiveness in daily-use products. In this study, we demonstrated the synthesis of silica core–shell microcapsules designed for controlled fragrance release in topical formulations. The microcapsules were synthesized via the sol–gel polymerization of tetraethyl orthosilicate (TEOS) on the surface of an oil/water emulsion, leveraging the shrinkage and deformation characteristics of sol–gel-derived silica during drying. The concentrations of dipalmitoylethyl dimethylammonium chloride, a cationic emulsifier used in cosmetics, and TEOS were optimized to sustain fragrance release for up to 24 h after topical application. An additional silica coating on the microcapsules reduced the Brunauer–Emmett–Teller surface area by 76.54%, enhancing fragrance stability for long-term storage. The timed-release behavior was assessed using fragrance evaluation tests and gas chromatography–mass spectrometry. The fragrance intensity and release profiles confirmed the potential of these microcapsules in daily-use cosmetics. These findings suggest that silica microcapsules with extended-release properties have application potential in both cosmetic and pharmaceutical products.